Cognitive Emotion Regulation Strategies as Predictors of Academic Achievement among University Students - Ghaleb Al-badareen (Sultan Qaboos University, 2016)
The purpose of this study was to investigate the impact of cognitive emotion regulation strategies on academic achievement of university students in Jordan. A random sample of 386 students from the Hashemite University participated in the current study. The Cognitive Emotion Regulation questionnaire was used to measure the cognitive emotion regulation strategies. The findings of this study showed that cognitive emotion regulation strategies had significant joint effect and relative effect on academic achievement. It is hoped that this study will be beneficial to students and teachers in developing cognitive emotion regulation strategies for effective learning.